Human Adenovirus Type 7 Infections in Hubei, China During 2018-2019: Epidemic Features and Genetic Characterization of the Detected Viruses - Li, Ying; Wang, Decheng; Zhang, Jingjing; Huang, Peiqi; Du, Hui; Xu, Jiali; Chen, Hebin; Yan, Yi; Chen, Hongwei; Lu, Xiaoxia; Liu, Di (Frontiers in Cellular and Infection Microbiology, 2021)
Human adenoviruses (HAdVs) type 7 can cause severe respiratory disease. During December 2018-August 2019, HAdV-7 infection was identified in 129 patients in Wuhan Children’s Hospital, Hubei Province, China. Samples were collected from hospitalized children and metagenomic sequencing was applied to detect the HAdV infections. Hemophagocytic lymphohistiocystosis (HLH) related to HAdV infections was observed in some patients clinically and patients was divided into two groups based on this to test the differences among clinical indicators. Genome variation, in-silico restriction endonuclease analysis (REA) and phylogenetic analyses were carried out to show the genome characterization of HAdV-7 in this study. It was found that many indicators, such as all blood routine indicators, in patients of HLH group showed significant levels. REA reveals that HAdV-7 in this study might belong to genome 7d and genome variation analysis displayed the stable genome of HAdV. HAdV-7 is still a threat to public, and global surveillance should be established.